Method of drawing elliptical points in the isometric form of a circle (Progress Annals: Journal of Progressive Research, 2023)
Creating ellipses dots from graphic method is offered in this article. In this case, the graphical method for constructing an ellipse is described in detail, and it is recommended to use it in modern architecture of buildings, since ellipsoids provide structural strength and have an excellent appearance